REVITALIZING THE ISLAMIC TRACES IN LUWU: UTILIZING THE ARCHAEOLOGICAL HERITAGE OF THE JAMI MOSQUE OF PALOPO IN LOCAL HISTORY LEARNING - Fitra Widya Wati (Kalyanamitra: Journal of Archaeological Resource Management, 2025)
This study examines the integration of the archaeological heritage of the Palopo Jami Mosque into local history learning to strengthen students’ cultural identity and historical understanding. The research aims to analyze how the mosque built in 1604 and representing early Islamic development in Luwu, can serve as a primary learning resource within contextual and site-based educational approaches. Using a qualitative descriptive design, data were gathered through field observations, interviews with educators and cultural practitioners, and analysis of historical and archaeological documents. The findings indicate that although the mosque possesses extraordinary historical, architectural, and pedagogical value, its educational utilization remains limited due to insufficient teaching materials, lack of teacher training, and weak institutional collabration. Nevertheless, direct engagement with the site significantly enhances students’ historical thinking, interpretation of artifacts, and appreciation of cultural continuity. The study concludes that integrating archaeological heritage into local history curricula can revitalize Islamic traces in Luwu while promoting culturally grounded, inquiry-based learning